PEMILIHAN ALTERNATIF KEBIJAKAN PENGELOLAAN SUMBERDAYA ENERGI PANAS BUMI DI KAMOJANG, JAWA BARAT DENGAN ANALISIS MULTI CRITERIA DECESION MAKING (MCDM) - Cepi Al Hakim; Akhmad Fauzi; Meti Ekayani (Departemen Ekonomi Sumberdaya dan Lingkungan, Fakultas Ekonomi dan Manajemen, Institut Pertanian Bogor, 2014)
Indonesia has geothermal potential equal to 29.038 MWe. As a clean renewable source of energy, geothermal is an alternative to the non-renewable fossil fuel which brings environmental impact such as carbon dioxide, one of the greenhouse gasses. Geothermal management in Kamojang is located in forest area; consists of 48,86 ha of conservation forest under the West Java Natural Resources Conservation Agency (BKSDA) management, and 46,50 ha of protection forest under the Perum Perhutani (state-owned forestry enterprise) management. The laws that directly regulate geothermal management in Kamojang are Law Number 5/1990 on Conservation of Natural Resources and its Ecosystem, Law Number 41/1999 on Forestry, Law Number 21/2014 on Geothermal, and West Java Regional Regulation Number 6/2006 on Geothermal Management. Determining alternatives for policy on geothermal management considers four aspects; economic, environmental, social and institutional/regulation. The analysis conducted were direct economic value analysis of geothermal, depletion value of geothermal and forest, conflict analysis, and stakeholder analysis. Determining alternatives for policy was done through Multi Criteria Decision making Analysis (MCDM).